Language change in a constructional network: the emergence of Mandarin [bi N hai N] comparative constructions - Liu Meili; Cuyckens Hubert; Zhan Fangqiong (Cognitive Linguistics)
This paper explores the mechanisms of and motivations for two unconventional comparative constructions in Mandarin: [bi Ni hai Ni] and [bi Ni hai Nj]. They are unconventional in that the item expressing the dimension along which the comparison is made is a noun rather than an adjective. It is shown that [bi Ni hai Ni] emerges (i) by analogy with the conventional comparative construction [bi N hai A] and (ii) by inheriting the nominal feature from an existing construction [Adverb N], which is corroborated by a collexeme analysis. At a more schematic level, the extension A > N observed in [bi N hai A] > [bi Ni hai Ni] may have been modeled on the existing development from [Adverb A] to [Adverb N]. Analogical extension and inheritance also underlie the subsequent development from [bi Ni hai Ni] to [bi Ni hai Nj]. This study not only shows how language changes in a constructional network (including node creation and network reconfiguration), but also sheds light on the nature of horizontal links. It also demonstrates how a synchronically perceived relation between constructions may impact a later, similar language change.